Is YoutubeTM an accurate source of patient-information for awareness about periodontal diseases? - Berceste Güler; Büşra Özaltun (University Library System, University of Pittsburgh, 2021)
Objectives: Oral hygiene education and patient awareness are crucial for prevention and the sustainability of its treatment because of high prevalence of periodontal diseases. This study aimed to evaluate YouTube videos related to periodontal diseases and assess them comprehensively, reliability, and quality for non-professional internet users. Methods: YouTube search was performed using the three keywords: 'periodontal disease', 'gingival disease,' and 'gum disease'. Video lengths, duration, numbers of total views, likes, dislikes, comments values were recorded. The interaction index, viewing rates and video power index (VPI) were calculated. Comprehensiveness tailor-made index was assessed for content, Global Quality Scale (GQS), and DISCERN scales were used for reliability and quality of videos. Results: A total of 210 videos were evaluated, and 79 videos were included in the study. While 69 of the videos are useful videos, 9 of them have misleading video content. VPI values were found 2.88±0.67 for useful videos and 1.78±0.66 for misleading videos. The mean GQS value of the videos has seen as 2.76±0.7. According to the DISCERN score, 41.8% of the videos show poor quality. The number of videos with comprehensiveness value (2) score is 44 and the number of videos (1) score is 35. Conclusions: YouTube videos may be used as an education source about periodontal disease for non-professional users; however, videos need to be improved in terms of content and quality. These and similar publications may be supported for the optimization of videos to be shared on YouTube with periodontal disease and oral hygiene education.